Going Native: South Park Satire, Settler Colonialism, and Hawaiian Indigeneity. (February 2017) - Maile, David Uahikeaikalei'ohu
In South Park 's "Going Native, " the white character Butters becomes inexplicably angry only to uncover that his family contends the anger is "biologically" caused by their "ancestral" belonging to Hawai'i. He then travels to Kaua'i to resolve this anger by connecting with his "native" home. To parody the materiality of white settlers playing and going native, Butters is represented as "native Hawaiian." This parody functions as a satire to ridicule and criticize settler colonialism in Hawai'i. Yet, it does so by distorting, dismembering, and erasing Hawaiian Indigeneity. By deploying an Indigenous-centered approach to critical theory, I analyze South Park 's "Going Native" as a popular culture satire to make three arguments. First, "Going Native" produces Indigeneity in racialized, gendered, and sexualized (mis)representations. The representations of "native Hawaiians" recapitulate marginalizing misrepresentations of Native Hawaiians, which inverts the parody. Second, as the parody breaks down, "native Hawaiians" reify settler colonialism. South Park 's satire fails and becomes haunted by specters of settlement that call into question its critique. When the "native Hawaiians" eventually liberate themselves from encroaching tourists and U.S. military forces, an impasse emerges. Rather than signifying Native Hawaiians with agency, only "native Hawaiians" demonstrate the possibilities of self-determination, sovereignty, and decolonization, which exempt white settlers from enacting colonization and produce a discursive impossibility for Native Hawaiians. Third, I suggest cultural studies reimagine its scholarship to exercise an alliance politics that interrupts knowledge produced by popular culture satire attempting critiques of settler colonialism that simultaneously naturalize the dispossession and elimination of Indigenous peoples.